The impact of ambiguous economic news on uncertainty and consumer confidence - Svensson, Helle Mølgaard and Albæk, Erik and van Dalen, Arjen and de Vreese, Claes H (European Journal of Communication, 2017)
Journalistic practice emphasizes both positive and negative aspects of news stories. Nevertheless, the effects of ambiguous news, which includes both positive and negative information, are under-investigated. This study examines how exposure to ambiguous economic news affects uncertainty and ‘consumer confidence’. Consumer confidence refers to citizens’ evaluations of their personal economic situation and of the national economy and is an antecedent of economic behaviour. Using a two-wave national panel survey and a media content analysis, the study demonstrates that ambiguous news exposure and individual level changes in consumer confidence are linked. Our analysis suggests that the relation between exposure to ambiguous news and changes in consumer confidence is mediated by economic uncertainty. This article bridges insights from research on consumer confidence, economic psychology and media effects and unravels one of the mechanisms at play in this cross-field.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMjY3MzIzMTE2Njc3MjA1